2021
DOI: 10.47352/jmans.v1i2.88
|View full text |Cite
|
Sign up to set email alerts
|

Review on Importance of Artocarpus heterophyllus L. (Jackfruit)

Abstract: The Jackfruit (Artocarpus heterophyllus L.) is well-known as “poor man’s food” fruit in Bangladesh. It is widely consumed by most of the rural people and it is the national fruit of Bangladesh. The main aim of this review is to document the medicinal significance of jackfruit (Artocarpus heterophyllus L.), major parts and uses of the jackfruit in Bangladesh. This article was based on mostly a literature review. All parts of the fruit and plant are used as human food, animal feed and wood source for furniture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 56 publications
0
12
0
2
Order By: Relevance
“…The edible portion of the fruit was 52.5% ( Table 1 ). A large body of literature has revealed that jackfruit is a rich source of carbohydrates, minerals, carboxylic acids, dietary fiber, vitamins and minerals and bioactive compounds ( Azad et al., 2007 ; Khan et al., 2021 ). Clearly, BARI Kanthal-3 is an extremely high yielding (ca.…”
Section: Resultsmentioning
confidence: 99%
“…The edible portion of the fruit was 52.5% ( Table 1 ). A large body of literature has revealed that jackfruit is a rich source of carbohydrates, minerals, carboxylic acids, dietary fiber, vitamins and minerals and bioactive compounds ( Azad et al., 2007 ; Khan et al., 2021 ). Clearly, BARI Kanthal-3 is an extremely high yielding (ca.…”
Section: Resultsmentioning
confidence: 99%
“…This is because if an exotic species is detected colonising a natural habitat, population structure indicates the demographic future of the species (Bruna & Kress, 2002). A. heterophylla (native to South East Asia; Khan et al, 2021), S. spectabilis (native to Central and South America; Irwin & Barneby, 1982) and T. superba (native to West and Central Africa; Orwa et al, 2009) had size class structures consistent with growing populations and therefore can be regarded as invasive in Mabira forest. These three species have also been reported to be invasive in several countries and islands around the world: A. heterophyllus in 24 countries, S. spectabilis in 32 countries, and T. superba in two countries (GBIF, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Some pests are attacked the home garden plant [1] [2]. some insects attract in the bean crop and pod [3]- [6], cinnamon plant and fruit [7], chrysanthemum crop and flower [8]; jackfruit plant and fruit [9] [10], mango plant and fruit [11], lemon plant parts [12], okra plant and fruit [13] [14] and so on [15]- [17]. The term is mostly secondhand for individuals that harm crops, cattle and animals, and forests or cause pain to people, especially in their town.…”
Section: Accepted Manuscriptmentioning
confidence: 99%